A national UK audit of suprapubic catheter insertion practice and rate of bowel injury with comparison to a systematic review and meta‐analysis of available research. Issue 8 (18th September 2019) - Hall, S.; Ahmed, S.; Reid, S.; Thiruchewam, N.; Sahai, A.; Hamid, R.; Harding, C.; Biers, S.; Parkinson, R.
Abstract: Objectives: Limited data exist on the risks of complications associated with a suprapubic catheter (SPC) insertion. Bowel injury (BI) is a well‐recognized albeit uncommon complication. Guidelines on the insertion of SPC have been developed by the British Association of Urological Surgeons, but there remains little evidence regarding the incidence of this complication. This study uses contemporary UK data to assess the incidence of SPC insertion and the rate of BI and compares to a meta‐analysis of available papers. Methods: National Hospital Episodes Statistics data were searched on all SPC insertions over an 18‐month period for operating procedure codes, Code M38.2 (cystostomy and insertion of a suprapubic tube into bladder). Patients age, 30‐day readmission rates, 30‐day mortality rate, and catheter specific complication rate were collected. To estimate the BI rate, we searched patients who had undergone any laparotomy or bowel operation within 30 days of SPC insertion. Trusts were contacted directly and directed to ascertain whether there was SPC‐related BI. PubMed search to identify papers reporting on SPC related BI was performed for meta‐analysis Results: 11 473 SPC insertions took place in the UK in this time period. One hundred forty‐one cases had laparotomy within 30 days. Responses from 114 of these cases reported one BI related to SPC insertion. Meta‐analysis showed an overall BI rate of 11/1490 (0.7%). Conclusions: This is the largest dataset reported on SPC insertions showing a lower than previously reported rate of BI. We recommend clinicians use a risk of BI of less than 0.25% when counseling low‐risk patients.